Application of Building Integrated Photovoltaic Electric System: Its Contribution in Reduction of Load Shedding Hours in Nepal - Shrestha, Jagan Nath (Journal of the Institute of Engineering, 2009)
Nepal, with a per capita energy consumption of about 15 GJ, is one of the five least energy consuming countries in the world. About 85% of its total energy comes from traditional energy sources such as fuel wood, agriculture residues and animal waste. This has led to grave consequences on ecological and environmental degradation. Keeping this in mind, GoN has provided policy guidelines in its Three Year Interim Plan (2007/08-10/11) to encourage the development and application of Renewable Energy Technologies such as photovoltaic power systems. This paper contains a brief account of the survey of PV powered solar home, telecommunication, civil aviation and water pumping systems in different parts of Nepal. As of July 15, 2008, about 6 MWp of PV power has been already installed in 67 districts of Nepal. The paper indicates on how load shedding hours could be reduced to some extent if Building Integrated Photovolatic Electric System (BIPVES) is introduced in different major cities of Nepal. The paper concludes that BIPVES systems be installed and awareness programmes on application of these systems are needed for different levels of people so that the quality of life could be improved. Key words: energy resources, building integration, urban renewable energy policy Journal of the Institute of Engineering, Vol. 7, No. 1, 2009 July, page: 1-5 doi: 10.3126/jie.v7i1.2056